The impact of school uniforms on primary school student's physical activity at school: outcomes of a cluster randomized controlled trial - Nicole Nathan; Nicole McCarthy; Kirsty Hope; Rachel Sutherland; Christophe Lecathelinais; Alix Hall; Cassandra Lane; Stewart Trost; Sze Lin Yoong; Luke Wolfenden (BMC, 2021)
Abstract Background Many school-based physical activity (PA) interventions are complex and have modest effects when delivered in real world contexts. A commonly reported barrier to students' PA, particularly among girls, are uniforms that are impractical (e.g. tunic/dress and black leather shoes). Modifying student uniforms may represent a simple intervention to enhance student PA. The primary aim of this trial was to assess the impact of a PA enabling uniform intervention (shorts, polo shirt and sports shoes) on girls' moderate-to-vigorous physical activity (MVPA) and total PA i.e. counts per minute (cpm). Methods A cluster randomized controlled trial was undertaken in 42 primary schools in New South Wales, Australia. Schools were randomized on one school day to the intervention group, where students wore a PA enabling uniform (their sports uniform) or a control group, where students wore their usual traditional uniform. Student PA was measured using wrist-worn Actigraph GT3X and GT9X accelerometers. Linear mixed models controlling for student characteristics were used to examine the effects of the intervention.. Results Of the 3351 eligible students, 2315 (69.1%) had parental consent and 2180 of these consenting students participated (94.2%) of which 1847 (84.7%) were included in the analysis. For the primary aim the study found no significant differences between girls at schools allocated to the intervention relative to the control on change in MVPA (0.76 min, 95% CI − 0.47 to 1.99, p = 0.22) or cpm (36.99, 95% CI − 13.88 to 87.86, p = 0.15). Exploratory analysis revealed small effects for a number of findings, including significant reduction in sedentary activity (− 1.77, 95% CI − 3.40 to − 0.14, p = 0.035) among all students at schools allocated to the intervention, and non-significant improvements in girls' light intensity PA (1.47 min, 95% CI − 0.06 to 3.00, p = 0.059) and sedentary activity (− 2.23 min; 95% CI − 4.49 to 0.02, p = 0.052). Conclusion The findings suggests that the intervention may yield small improvements in some measure of PA and require substantiation in a larger RCT with longer-term follow-up. The inclusion of additional intervention components may be required to achieve more meaningful effects. Trial registration The trial was prospectively registered with Australian New Zealand Clinical Trials Register ACTRN12617001266358 1st September 2017.